State, sustainable development and governance in brazil: Public policies for energy and water post rio-92 - Peguim, Cássia Natanie [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2020)
In order to understand how the concept of sustainable development was incorporated into public policies for the management of natural resources for energy generation, let’s take water as an example and analyze the issue based on the discussion on public and private conception of governance as the action of the state in the elaboration of public policies. The space and time of the analysis is Brazil, after the United Nations Conference on Environment and Development, Rio 92, characterized by the neoliberal reform initiated by Fernando Collor de Mello and the resumption of the creation of state--owned companies dealing with the use of natural resources in Brazil, interacting with the market during Luís Inácio Lula da Silva and Dilma Rousseff’s government. The creation of a contemporary institutional structure in accordance with the principles of sustainable development has brought with it the problem of a change in the perception of the value of water use and exchange, in which the issue of access, considering a relation between unequal, present in state management, and between equals, in Civil society participates in the redefinitions that occurred since 1992, when the concept was spread. The concept of sustainable development is inseparable from the problem of the use of natural resources, which position, either towards the market or the state, oscillates between and within state actions with regard to its position as an economic agent.
Estado, desenvolvimento sustentável e governança no brasil: Políticas públicas para energia e água pós rio-92
Keywords: Brazil; Public policy; Sustainable development